Studying farm insurance demand under financial constraints - Lajos Baráth; Raushan Bokusheva; Imre Fertő (Hungarian Academy of Sciences, Institute of Economics, 2016)
We hypothesize a reciprocal causation between crop insurance use and the economic performance of farms in an environment characterized by imperfect financial markets and farms' budget constraints. To test our hypothesis, we apply a system of simultaneous equations consisting of economic performance and insurance demand models to the case study of Hungarian cropping farms. In addition, considering that insured farms may have better access to external finance, we seek empirical evidence confirming a potential positive effect of crop insurance on the economic performance of financially constrained farms. Our study results indeed confirm the reciprocal causation hypothesis.
Keywords: G22; L25; Q12; Q14; 330; crop insurance demand; farm productivity; financial constraints; farm investment; Hungarian agriculture